Numerical study of cooling photovoltaic panels with air exhausted from industrial systems: Comparisons and innovative configurations - Wassim Salameh; Jalal Faraj; Mahmoud Khaled (International Journal of Thermofluids, 2023)
Utilizing a cooling technique can help prevent overheating, which can have a detrimental impact on the performance of solar panels. Instead of using a water cooling system that requires a pump, an alternative method uses the return air from a Heating, Ventilating, and Air Conditioning (HVAC) system often utilized in industrial settings. An air cooling system that uses the HVAC system's return air was previously recommended by the co-authors of the current study. Using numerical methods, they carried out a feasibility analysis and showed how a variety of parameters, such as the convection coefficient and the flow type (natural or forced), might affect the output power (efficiency) of the system. As a continuation of the previous study, the present study examines two cooling scenarios to further their past findings. Three different configurations for external flow were tested: cooling the upper and lower surfaces of the PV with exhaust air, installing a vortex generator at the leading edge of the lower surface while relying on natural convection for the upper part, and installing a vortex generator on both the upper and lower surfaces. The efficiency of the PV system increases from 11 % to 18 % with an increase in cooling demand from 0 to 160 kW with solar radiation of 500 W/m2. Efficiency was improved by generating turbulent flow at the leading edge of the panel. While using an internal flow on the bottom surface, the system's efficiency increased as the PV module's length increased.